Highlighting areas of focus regarding emerging Customs-related challenges in Humanitarian Logistics and the Relief-Chain: A Perspective from Pakistan - Ahsen, Saad Raafay (2016)
The purpose of this paper is to determine whether Customs-related challenges in the Relief Chain, emanating out of Pakistan, are different from the current international consensus on what these challenges entail. Customs is one of the most crucial links in the Relief Chain, having a direct impact on the pace of the humanitarian response in a disaster affected area. It thus becomes critical to study Customs-related challenges in Humanitarian Logistics, which by its very definition aims to provide humanitarian relief in an efficient, cost-effective and hence rapid fashion. This is especially relevant for Pakistan, which is a country with a long history of disasters, both natural and man-made.